2020
DOI: 10.1590/s0102-053620200217
|View full text |Cite
|
Sign up to set email alerts
|

Sources and splitting of the organic fertilization in top dressing in cabbage production

Abstract: ABSTRACT Although there exist researches about fertilization in top dressing in the production of cabbage, these are usually made with inorganic fertilizers, being rare the researches with organic fertilization in top dressing in the production of most vegetables. The objective was to evaluate the effect of different splitting of two organic fertilizers in top dressing in the production of cabbage. Six treatments were evaluated, with four replications in randomized block design. The six treatments were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Production increases with the use of these organic fertilizers have been reported in several vegetables grown under tropical and subtropical conditions (Lanna et al, 2017;Silva et al, 2018;Souto et al, 2018;Cardoso et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Production increases with the use of these organic fertilizers have been reported in several vegetables grown under tropical and subtropical conditions (Lanna et al, 2017;Silva et al, 2018;Souto et al, 2018;Cardoso et al, 2020).…”
Section: Resultsmentioning
confidence: 98%
“…In organic fertilizers rich in nitrogen such as castor Nepomuceno Alves et al (2024) Organic fertilizer doses for top-dres... bean cake and hoof and horn powder, fertilization should be applied in a way to avoid excess nutrients in the soil solution (Candian, 2018;. The speed of nutrient release by organic fertilizers should be according to the crop demand (Cardoso et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vimala, et al [25] and Hasan and Solaiman [26] also reported positive effect of the conjunctive use of organic and inorganic sources of nutrients on the growth and yield of cabbage (Brassica oleracea). Cardoso et al [27] studied two sources of organic fertilization in cabbage production and observed greater yield, head weight and diameter in case of use of castor bean cake compared to the organic compost. As stated by Ayilara et al [28], addition of activators (e.g.…”
Section: Head Yieldmentioning
confidence: 99%
“…As for most species, in chive there are no top-dressing organic fertilization recommendations, only inorganic ones. Among the options of organic fertilizers used by vegetable producers in top dressing application are castor bean cake and hoof and horn powder [12,13,11,3,8] Castor bean cake is widely used as a source of nitrogen, which is a nutrient that plants need in large quantities [11,9]. Organic residues from the processing and slaughter of cattle, sold in the form of hoof and horn powder is also an alternative source of nitrogen.…”
Section: Introductionmentioning
confidence: 99%